2017
DOI: 10.4103/0970-2113.201319
|View full text |Cite
|
Sign up to set email alerts
|

Cotton dust exposure: Analysis of pulmonary function and respiratory symptoms

Abstract: Background:Cotton industry workers are exposed to various hazards in the different departments of textile factories. The major health problems associated with cotton dust are respiratory problems, byssinosis, bronchitis and asthma.Objective:To study the effect of cotton dust exposure on pulmonary function and respiratory symptoms.Settings and Design:This cross-sectional observational study was conducted at cotton mill in the Ahmedabad city.Materials and Methods:One hundred cotton mill workers of the weaving an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
18
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 14 publications
9
18
2
3
Order By: Relevance
“…However, in the current study, the highest prevalence of chronic respiratory symptoms was reported among workers in the finishing department (71%). Studies conducted in textile factories have indicated that workers who have the longest period of service associated with chronic exposure have the highest risk of developing chronic respiratory health problems [4,5,15,30]. This has been confirmed in this study, where workers in the finishing department were the oldest and were senior to the spinning and weaving department workers.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…However, in the current study, the highest prevalence of chronic respiratory symptoms was reported among workers in the finishing department (71%). Studies conducted in textile factories have indicated that workers who have the longest period of service associated with chronic exposure have the highest risk of developing chronic respiratory health problems [4,5,15,30]. This has been confirmed in this study, where workers in the finishing department were the oldest and were senior to the spinning and weaving department workers.…”
Section: Discussionsupporting
confidence: 83%
“…These symptoms are known to occur among textile workers and correspond with the diagnosis of byssinosis [6]. This is also found in other recent studies of the textiles where these symptoms are reported to have high prevalence [4,5,.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…18 Furthermore, increased respiratory symptoms and pulmonary function abnormalities are higher in cotton workers compared with matched controls. 19 Therefore, cotton dust plays an important role in initiation of respiratory health problems. Higher FeNO levels and elevated respiratory symptoms observed in our study in pilgrims dressed in cotton towel ihrams might have been due to the cotton fibers generated from the ihrams, in addition to other factors.…”
Section: Discussionmentioning
confidence: 99%